Fluorescent glass for mid-infrared luminescence and preparation method thereof
By mixing and sintering the phosphor with sulfhydryl glass powder, the problems of poor mechanical properties and complex preparation process of sulfur-based glass are solved, and the low-cost and simple preparation of high-performance mid-infrared fluorescent glass is achieved, and the strong 2.65μm fluorescent output is achieved. and wide luminous bands.
Patent Information
- Application Number
- CN202411017843.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-07-26
AI Technical Summary
The existing sulfur-based glass has poor mechanical properties in the field of mid-infrared luminescence, and the preparation process is complex and costly, making it difficult to take into account high performance, simple process and low cost.
Mix the phosphor with sulfhydryl glass powder and sintered at lower temperatures, simplifying the process flow, reducing preparation time and cost, and leveraging the high brightness of the phosphor and the low phonon energy of the sulfuryl and halogen glass and excellent mid-infrared light transmission performance.
The strong 2.65μm room temperature fluorescence output is generated under the 980nm laser pump, which realizes simple and efficient mid-infrared fluorescent glass synthesis, expands the selection range of phosphors, and has significant economic benefits.
Smart Images

Figure CN119118489A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a fluorescent glass for mid-infrared luminescence and a preparation method thereof, belonging to the technical field of optical materials. Background Art
[0002] The mid-infrared (MIR) band mainly includes light sources in the range of 2-5 μm. This band has shown significant application potential in the fields of spectroscopy, biosensors, medical diagnosis, environmental detection and gas sensing, and has attracted widespread attention from researchers around the world. In particular, many pollutant gases in the atmosphere have vibration absorption characteristics in the infrared region (for example, CH 4 :~3.3μm, H 2 S: 2.7 μm, NH 3 :2.3μm), which makes the development of 2-5μm mid-infrared light source of great scientific significance and practical value. Chalcogenide glass is mainly composed of sulfides and selenides composed of group VI elements such as sulfur (S), selenium (Se), tellurium (Te), and heavy metal elements such as germanium (Ge), gallium (Ga), and arsenic (As). Due to its high third-order nonlinear coefficient and low phonon energy (<350cm -10 ), high refractive index (>2.1) and wide infrared transmittance range. Chalcogenide glass has a wide spectral range, covering the near-infrared, mid-infrared and far-infrared bands. Therefore, chalcogenide glass is considered to be the most ideal transmission medium in the mid-infrared and far-infrared bands. Although chalcogenide glass has good chemical and thermal stability, its mechanical properties are poor, which limits the potential application prospects of chalcogenide glass. In order to solve this problem, researchers introduced high-bond energy halogens as glass network modifiers to increase the packing density of the glass, thereby improving the stability of the glass network structure. The mechanical properties of chalcogenide glass can be improved by optimizing the glass process to reduce lattice defects or bond defects in chalcogenide glass. However, the preparation process of chalcogen-halide glass is relatively complicated and requires a long time period and high experimental conditions. Summary of the invention
[0003] In order to solve the problem that it is difficult to achieve high performance, simple process and low cost in the existing technology of mid-infrared luminescent fluorescent glass, the present application provides a fluorescent glass for mid-infrared luminescence and a preparation method thereof, in which phosphor and sulfide glass powder are mixed and ground, and then sintered together at a lower temperature, so that fluorescent glass with mid-infrared luminescence characteristics can be prepared in a shorter time and at a lower cost, and the high brightness, wide color gamut and high stability of the phosphor, as well as the low phonon energy and excellent mid-infrared transmittance of the sulfide glass are fully utilized.
[0004] This application adopts the following technical solutions:
[0005] A method for preparing fluorescent glass for mid-infrared luminescence comprises the following steps:
[0006] S1, respectively obtaining phosphor powder and sulfur-halide glass powder;
[0007] S2. Grinding, pressing and calcining the mixture containing the fluorescent powder and the sulfur-halide glass powder to obtain the fluorescent glass for mid-infrared luminescence.
[0008] Optionally, the preparation method of the phosphor is:
[0009] Will contain A 2 O 3 , B 2 O 3 , X 2 O 3 The fluorescent powder raw material is calcined and then ground to obtain the fluorescent powder;
[0010] A is Y and / or Gd;
[0011] B is Ga and / or Al;
[0012] X is Er and / or Tm.
[0013] Optional, A 2 O 3 , B 2 O 3 , X 2 O 3 The molar ratio is 0.56~0.6:1:0.032~0.16.
[0014] Optional, A 2 O 3 , B 2 O 3 , X 2 O 3 The molar ratio is 35-37.5:62.5:2-10.
[0015] Optionally, the conditions of the roasting I include:
[0016] The temperature of calcination I is 1000°C-1600°C;
[0017] The calcination time is 1 h to 6 h.
[0018] Optionally, the conditions of the roasting I include:
[0019] The temperature of calcination I is 1550°C-1580°C;
[0020] The calcination time is 3h-5h.
[0021] Optionally, the preparation method of the sulfide-halide glass powder is:
[0022] Containing Ga 2 S 3 , Sb 2 S 3 , CsCl sulfide glass powder raw materials are placed in a vacuum sealed container, roasted II, quenched, annealed and then ground to obtain the sulfide glass powder.
[0023] Optionally, the molar amounts of the components in the sulfide-halide glass powder raw material are:
[0024] Ga 2 S 3 30-40 mole parts;
[0025] Sb 2 S 3 20-70 mole parts;
[0026] CsCl 20-70 molar parts.
[0027] Optionally, the conditions of the roasting II include:
[0028] The temperature of calcination II is 900°C-1000°C;
[0029] The calcination time of II is 8h-15h.
[0030] Optionally, the conditions of the roasting II include:
[0031] The temperature of calcination II is 920°C-950°C;
[0032] The calcination time of II is 10h-14h.
[0033] Optionally, the quenching conditions include: cooling to 800°C to 900°C after calcination II, placing the vacuum sealed container in a room temperature environment until it drops to room temperature;
[0034] Preferably, the annealing conditions include:
[0035] The annealing temperature is 200°C-350°C;
[0036] The annealing time is 4h to 8h.
[0037] Optionally, the vacuum degree of the vacuum sealed container is 10 -1 Pa-10 -3 Pa. Preferably 10 -3 Pa.
[0038] Optionally, the calcination conditions include:
[0039] The calcination temperature is 450°C-600°C;
[0040] The calcination time is 3h-6h.
[0041] Optionally, the calcination conditions include:
[0042] The calcination temperature is 500°C-530°C;
[0043] The calcination time is 3h-4h.
[0044] The synthesis process of sulfide-halide glass in the prior art requires vacuum, calcination and annealing, while the synthesis of fluorescent glass in the present application only requires mixing and grinding glass powder and fluorescent powder, pressing into sheets and sintering, without vacuum and annealing.
[0045] The beneficial effects of this application include:
[0046] The fluorescent glass for mid-infrared luminescence provided by the present application combines the high brightness, wide color gamut and high stability of the phosphor, and the low phonon energy and excellent mid-infrared light transmittance of the sulfide glass. Under 980nm laser pumping, the fluorescent glass can produce strong 2.65μm room temperature fluorescence output. The preparation method of the present application can prepare a fluorescent glass material with a wide luminous band in a short time and at a low cost. It is a simple and efficient method for synthesizing mid-infrared fluorescent glass, and can expand the selection range of phosphors, with significant economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 Y 3 Ga 5 O 12 X-ray diffraction patterns of phosphors and phosphor glasses.
[0048] Figure 2 This is a fluorescence spectrum diagram of the fluorescent glass of specific embodiment 1 in the mid-infrared region. DETAILED DESCRIPTION
[0049] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0050] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0051] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.
[0052] The X-ray diffraction instrument in the embodiment of the present application is a Japanese Rigaku-miniflex600 X-ray polycrystalline diffractometer, the test conditions are Cu target, the test range is 10-80°, 5° / min. The fluorescence performance test uses an FLS920 (Edinburgh) fluorescence spectrometer, and the test conditions are an excitation wavelength of 980nm.
[0053] Example 1
[0054] Y, Ga, Er with a purity of 99.9999% are 2 O 3 :Ga 2 O 3 :Er 2 O 3 The molar ratio of 36.25:62.5:5 is accurately weighed and mixed to form the phosphor raw material. The powder raw material is evenly ground and placed in a crucible, which is then placed in a high-temperature furnace and heated to 1580°C and kept warm for 5 hours, then cooled to room temperature, and the agglomerated phosphor powder is taken out and ground in a mortar to obtain the desired phosphor powder.
[0055] The purity of 99.9999% Ga, Sb, Cs is Ga 2 S 3 :Sb 2 S 3 The molar ratio of CsCl to MgCl was 30:30:40, and the mixture was accurately weighed in a glove box and mixed to form a raw material of sulfidohalide glass powder. The raw material of sulfidohalide glass powder was placed in a clean quartz ampoule, sealed with a matching mechanical valve, and transferred to an automatic tube sealing machine for further processing. When the vacuum degree reached 10 -3 After Pa, the quartz ampoule is sealed with a hydrogen-oxygen flame gun. The cooled and sealed quartz ampoule is placed in a rocking furnace, heated to 920°C and kept for 10 hours for homogenization. Then the temperature is lowered to 850°C, the quartz ampoule is taken out and quickly placed in room temperature water for quenching. In order to eliminate stress, the quartz ampoule is placed in an annealing furnace and annealed for 6 hours at 30°C below the glass transition temperature. Finally, the final sulfide-halide glass powder is obtained by grinding.
[0056] The phosphor and sulfide glass powder were mixed and ground with anhydrous ethanol. Subsequently, the mixture was pressed into sheets using a Φ12 mold (10 MPa, 2 min), and then placed in a crucible and kept at 500 ° C for 3 h to obtain the phosphor glass. The visible mid-infrared emission spectra of the phosphor samples and the phosphor glass at room temperature were measured using an FLS920 fluorescence spectrometer, and it was observed that the central wavelength of the mid-infrared emission was 2.65 μm.
[0057] Example 2
[0058] The purity of 99.99% Gd 2 O3 , Ga 2 O 3 , Er 2 O 3 Press Gd 2 O 3 :Ga 2 O 3 :Er 2 O 3 The molar ratio of 35.25:62.5:1,25 is accurately weighed and mixed to form the phosphor powder raw material. The powder raw material is ground evenly and placed in a crucible. It is placed in a high-temperature furnace and heated to 1580°C and kept warm for 5 hours. It is then cooled to room temperature. The agglomerated phosphor powder is taken out and ground in a mortar to obtain the desired phosphor powder.
[0059] The purity of 99.9999% Ga, Sb, Cs is Ga 2 S 3 :Sb 2 S 3 The molar ratio of CsCl to MgCl was 35:35:30, and the mixture was accurately weighed in a glove box and mixed to form a sulfide glass powder raw material. The sulfide glass powder raw material was placed in a clean quartz ampoule, sealed with a matching mechanical valve, and transferred to an automatic tube sealing machine for further processing. When the vacuum degree reached 10 -3 After Pa, the quartz ampoule is sealed with a hydrogen-oxygen flame gun. The cooled and sealed quartz ampoule is placed in a rocking furnace, heated to 920°C and kept for 10 hours for homogenization. Then the temperature is lowered to 850°C, the quartz ampoule is taken out and quickly placed in room temperature water for quenching. In order to eliminate stress, the quartz ampoule is placed in an annealing furnace and annealed for 6 hours at 30°C below the glass transition temperature. Finally, the final sulfide-halide glass powder is obtained by grinding.
[0060] The phosphor and sulfide glass powder were mixed, and anhydrous ethanol was added for grinding. Subsequently, the mixture was pressed into sheets using a Φ12 mold (10 MPa, 2 min), and then placed in a crucible and kept at 500 ° C for 3 h to obtain the fluorescent glass. The visible and mid-infrared emission spectra of the fluorescent glass sample at room temperature were measured using an FLS920 fluorescence spectrometer, and it was observed that the central wavelength of the mid-infrared emission was 2.65 μm.
[0061] Example 3
[0062] The purity of 99.99% Y 2 O 3 , Ga 2 O 3 , Er 2 O 3 Press Y 2 O 3 :Ga 2 O 3 :Er2 O 3 The molar ratio of 36.25:62.5:1.25 is accurately weighed and mixed to form the phosphor raw material. The powder raw material is evenly ground and placed in a crucible, which is then placed in a high-temperature furnace and heated to 1580°C and kept warm for 5 hours, then cooled to room temperature, and the agglomerated phosphor is placed in a mortar and ground to obtain the desired phosphor.
[0063] The purity of 99.9999% Ga, Sb, Cs is Ga 2 S 3 :Sb 2 S 3 The molar ratio of CsCl and MgCl is 30:30:40, and the mixture is accurately weighed in a glove box and mixed to form a raw material of sulfur-halide glass powder. The raw material of sulfur-halide glass powder is placed in a clean quartz ampoule, sealed with a matching mechanical valve, and transferred to an automatic tube sealing machine for further processing. When the vacuum degree reaches 10 -3 After Pa, the quartz ampoule is sealed with a hydrogen-oxygen flame gun. The cooled and sealed quartz ampoule is placed in a rocking furnace, heated to 920°C and kept for 10 hours for homogenization. Then the temperature is lowered to 850°C, the quartz ampoule is taken out and quickly placed in room temperature water for quenching. In order to eliminate stress, the quartz ampoule is placed in an annealing furnace and annealed for 6 hours at 30°C below the glass transition temperature. Finally, the final sulfide-halide glass powder is obtained by grinding.
[0064] The phosphor powder and sulfur-halide glass powder were mixed and ground with anhydrous ethanol. Subsequently, the mixture was pressed into a sheet using a Φ12 mold (10 MPa, 2 min), and then placed in a crucible and kept at 500 ° C for 3 h to obtain the fluorescent glass. 3 Ga 5 O 12 X-ray diffraction patterns of phosphors and fluorescent glass are shown below: Figure 1 As shown, the visible mid-infrared emission spectra of the phosphor samples and fluorescent glass at room temperature were measured by FLS920 fluorescence spectrometer. Figure 2 As shown, the central wavelength of mid-infrared emission can be observed to be 2.65
[0065] Example 4
[0066] The purity of 99.99% Gd 2 O 3 , Ga 2 O 3 、Tm 2 O 3 Press Gd 2 O 3 :Ga 2 O 3 :Tm 2 O 3The molar ratio of 35.25:62.5:1.25 is accurately weighed and mixed to form the phosphor raw material. The powder raw material is evenly ground and placed in a crucible, which is then placed in a high-temperature furnace and heated to 1580°C and kept warm for 5 hours, then cooled to room temperature, and the agglomerated phosphor powder is taken out and ground in a mortar to obtain the desired phosphor.
[0067] The purity of 99.9999% Ga, Sb, Cs is Ga 2 S 3 :Sb 2 S 3 The molar ratio of CsCl to MgCl was 35:35:30, and the mixture was accurately weighed in a glove box and mixed to form a sulfide glass powder raw material. The sulfide glass powder raw material was placed in a clean quartz ampoule, sealed with a matching mechanical valve, and transferred to an automatic tube sealing machine for further processing. When the vacuum degree reached 10 -3 After Pa, the quartz ampoule is sealed with a hydrogen-oxygen flame gun. The cooled and sealed quartz ampoule is placed in a rocking furnace, heated to 920°C and kept for 10 hours for homogenization. Then the temperature is lowered to 850°C, the quartz ampoule is taken out and quickly placed in room temperature water for quenching. In order to eliminate stress, the quartz ampoule is placed in an annealing furnace and annealed for 6 hours at 30°C below the glass transition temperature. Finally, the final sulfide-halide glass powder is obtained by grinding.
[0068] The phosphor and sulfide glass powder were mixed, and anhydrous ethanol was added for grinding. Subsequently, the mixture was pressed into sheets using a Φ12 mold (10 MPa, 2 min), and then placed in a crucible and kept at 500 ° C for 3 h to obtain the fluorescent glass. The visible and mid-infrared emission spectra of the fluorescent glass sample at room temperature were measured using an FLS920 fluorescence spectrometer, and it was observed that the central wavelength of the mid-infrared emission was 2.65 μm.
[0069] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing fluorescent glass for mid-infrared luminescence, characterized in that: The steps include: S1, respectively obtaining phosphor and sulfur-halide glass powder; S2. Grinding, pressing and calcining the mixture containing the fluorescent powder and the sulfur-halide glass powder to obtain the fluorescent glass for mid-infrared luminescence.
2. The preparation method according to claim 1, characterized in that: The preparation method of the phosphor is as follows: The phosphor powder raw material containing A2O3, B2O3 and X2O3 is calcined and then ground to obtain the phosphor powder; A is Y and / or Gd; B is Ga and / or Al; X is Er and / or Tm.
3. The preparation method according to claim 2, characterized in that: The molar ratio of A2O3, B2O3 and X2O3 is 0.56~0.6:1:0.032~0.
16.
4. The preparation method according to claim 2, characterized in that: The conditions of the calcination I include: The temperature of calcination I is 1000°C-1600°C; The calcination time is 1 h to 6 h.
5. The preparation method according to claim 1, characterized in that: The preparation method of the sulfide-halide glass powder is as follows: The sulfide-halide glass powder raw material containing Ga2S3, Sb2S3 and CsCl is placed in a vacuum sealed container, roasted II, quenched, annealed and then ground to obtain the sulfide-halide glass powder.
6. The preparation method according to claim 5, characterized in that: The molar amounts of the components in the sulfide-halide glass powder raw material are: Ga2S3 30-40 mol parts; Sb2S3 20-70 mol parts; CsCl 20-70 molar parts.
7. The preparation method according to claim 5, characterized in that: The conditions of the calcination II include: The temperature of calcination II is 900°C-1000°C; The calcination time of II is 8h-15h.
8. The preparation method according to claim 1, characterized in that: The quenching conditions include: cooling to 800°C to 900°C after roasting II, placing the vacuum sealed container in a room temperature environment until it drops to room temperature; Preferably, the annealing conditions include: The annealing temperature is 200°C-350°C; The annealing time is 4h to 8h.
9. The preparation method according to claim 1, characterized in that: The vacuum degree of the vacuum sealed container is 10 -1 Pa-10 -3 Pa.
10. The preparation method according to claim 1, characterized in that: The calcination conditions include: The calcination temperature is 450°C-600°C; The calcination time is 3h-6h.
Citation Information
Patent Citations
Colored phosphor powder in use for field emission, and preparation method
CN101050360A
Red fluorescent glass ceramic and preparation method thereof
CN108249765A
Red fluorescent powder for ultraviolet LED and preparation method thereof
CN109370591A
Chromium-doped ultra-wideband near-infrared fluorescent material and preparation method thereof
CN118206991A
Glass light-emitting device
JP1994216408A
